Performance evaluation of the Molbio diagnostics Truenat MTB Ultima/COVID-19 multiplex assay for TB and COVID-19 case detection among people with symptoms suggestive of tuberculosis—a study protocol for clinical trials - Manju Purohit; Manju Purohit; Willy Ssengooba; Helen Cox; Cesar Ugarte-Gil; Cesar Ugarte-Gil; James Sserubiri; Hafsah Tootla; Hafsah Tootla; Kavindhran Velen; Rita Székely; Adam Penn-Nicholson (Frontiers in Public Health)
BackgroundTuberculosis (TB) remains a major public health problem globally, as reflected in persistently high morbidity and mortality rates. Current control efforts have been further complicated by the ongoing SARS-CoV-2 (COVID-19) pandemic. Rapid molecular diagnostics remain crucial to identifying the millions of people with undiagnosed TB.ObjectivesThe study aimed to determine the diagnostic accuracy of Truenat MTB Ultima/COVID-19 for the detection of COVID-19 and TB among presumptive TB participants, using a microbiological reference standard (MRS) and a country-approved real-time reverse transcription polymerase chain reaction (RT-PCR) COVID-19 assay.MethodsThis prospective cohort study assessed the diagnostic accuracy of the Truenat MTB Ultima/COVID-19 multiplex test among adults with presumptive TB, enrolled from healthcare facilities in four countries, aiming to reach 270 confirmed TB cases. The inclusion criteria were as follows: adults who self-reported at least one symptom suggestive of pulmonary TB, were willing to return for a day 2 visit, and agreed to provide oral swab samples for bio-banking. Patients were excluded from enrolment in the study if they had started anti-TB treatment within 60 days or TB preventive therapy within 6 months prior to enrolment or if they were unable to provide 3 mL of sputum or nasopharyngeal (NP) and tongue swab samples.Expected outcomeThis study expected to obtain point estimates of the sensitivity and specificity of the Truenat MTB Ultima/COVID-19 multiplex test for TB and COVID-19 detection, compared to Xpert Ultra, among presumptive TB participants using an MRS and pre-defined COVID-19 assay.